معرفة الذات الإلهية بين رؤية المتكلمين وفي منظور تصوف ابن العربي (مجلة الواحات للبحوث والدراسات, 2022)
ملخص: يُعنى هذا البحث بمحاولة بيان موقف ابن العربي النقدي من المتكلمين فيما يتعلق بمسألة مهمّة من مسائل الإلهيات وهي: معرفة الذات الإلهية. ويبدو أن هذا الموضوع يكتسب أهميته من خلال محاولة تقدير هذا النقد في إطار درس علاقة علم الكلام بالتصوف، والوقوف على بعض المآخذ الأساسية على علم الكلام من رؤية صوفية بحتة. وقد التزمت استخدام منهج استقرائي، وصفي، مقارن، وتحليلي. وخلص البحث فيما خلص إلى أن البحث الكلامي في مسألة معرفة الذات الإلهية في نظر ابن العربي يؤدي إلى الانحجاب عن حقيقة العلم بالله تعالى أو المعرفة الإلهية وإعطائها حقها المرتبط أصلاً بالإيمان المثمر للتقوى والعمل الصالح. كما أن من أهم الآفاق التي يحاول أن يفتحها هو محاولة جسر الهوة بين علم الكلام والتصوف، والبحث عن جوانب التكامل المعرفي بين العلمين، إضافة إلى محاولة تجديد علم الكلام في إطار الهندسة الروحانية للتصوف الإسلامي.كلمات دالة: 1- الذات الإلهية. 2- ابن العربي.3– المتكلمون.4–التصوف.      Abstract:This research deals with the attempt to shed light on the critical position of Ibn al-Arabi on theologians with regard to a significant divine issue: knowledge of the Divine Self. It seems this topic is gaining momentum through the attempt to assess such criticism by looking into the link between theology and Sufism to find out some weak basic points of theology from a purely Sufism perspective. I have strictly adopted an inductive, descriptive, comparative, and analytical approach. One of the conclusions the study reached that theological research on the question of Divine Self-knowledge in the eyes of ibn al-Arabi leads to detachment from the truth of knowledge of God Almighty or divine knowledge and giving it its right originally associated with the fruitful faith of piety and righteous deeds. Also, one of the most important prospects for research is could bridge the gap between theology and Sufism and offer us an innovative reading of theology. Key words: Divine self , Ibn al,Arabi, Theologians,Sufism